Evaluation of the Independent Curriculum at IT Baitul Hijrah Kindergarten, Binjai City Using the CIPP Model (Context, Input, Process, Product) - Budimayansah, Bambang Lestrika; Siregar, Andi Suhendra; Wijaya, Chandra (Al Qalam: Jurnal Ilmiah Keagamaan dan Kemasyarakatan, 2025)
The Independent Curriculum is implemented in TK IT Baitul Hijrah Kota Binjai using the CIPP (Context, Input, Process, Product) model as the initial step in this study. The purpose of the evaluation is to determine how well the Independent Curriculum supports early childhood education in terms of sustainability, relevance, and effectiveness. The context element shows how the school's vision and mission are in line with the values of the Independent Curriculum, which are strengthened by leading initiatives such as ProTaBa (Baby Tahfidz Program) and collaboration between institutions and external parties. Although most teachers meet the competency requirements in the input aspect, more training in educational technology and facility improvement are still needed. Positive interactions between teachers and students are evident in the process aspect, but the learning approach is still traditional with little integration of technology. According to the product evaluation, students' social and spiritual growth is quite important, although their Pancasila character has not been strengthened optimally. Strengths, opportunities, weaknesses, and threats in the implementation of the criteria are identified through a SWOT analysis. Intensive teacher training, purchasing digital resources, increasing character values in education, and fostering better parent collaboration are some of the suggested tactics. In conclusion, despite the benefits of the Independent Curriculum, a number of important areas require improvement to maximize the achievement of the country's educational goals.